The Effects Of Sleep Quality On Chronic Illness Management in Adults - Dian Suryani; Ridwan Prasetyo (International Journal of Health and Medicine, 2024)
This article investigates the relationship between sleep quality and the management of chronic illnesses such as diabetes and hypertension. By analyzing data from patient surveys and health records, the study finds that poor sleep quality is associated with worsened disease management and higher healthcare utilization. The findings suggest that improving sleep quality should be an integral part of chronic illness management strategies to enhance patient outcomes.